DETERMINATION OF THE TROPICAL STATUS OF FLOATING NET CAGE WATER BASED ON THE DISTRIBUTION OF NITROGEN, PHOSPHORUS AND CHLOROPHYLL-A - Peni Pujiastuti; Roesleini J Putri; Suseno Suseno (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
The dominant source of pollutants for floating net cages are fish feed and feces. They cause phosphorus and nitrogen in water increase, trigger eutrophication, marked by the appearance of algae. Algae are green plants, contain chlorophyll-a. The content of phosphorus, nitrogen and chlorophyll-a can be used to determine the tropical status of water. The objective of this research is to determine the tropical status of marine cage water. The research method was descriptive laboratory. Nitrogen content is measured as nitrite according to SNI 6989.9-2004, nitrate according to APHA Section 4500-NO3, ammonia according to SNI 19-1655-1989. Phosphorus analysis according to SNI 06-6989-31: 2005. Chlorophyll-a analysis used the Strickland & Parson method by spectrophotometry. Laboratory data were analyzed for tropical status based on nitrogen, phosphorus and chlorophyll-a content. The results showed that the tropical status of the KJA water of Gajah Mungkur Reservoir Wonogiri in the rainy season had eutrophic status, containing high levels of phosphorus and nitrogen elements. The eutrophic status indicated  that the water had been polluted by an enhancement of  nitrogen levels by 18.345 µg/L and phosphorus by 420.65 µg/L. These nitrogen and phosphorus pollutants increased the growth of chlorophyll-a by 12.70 µg/L.